Peningkatan Kemampuan Menempel Gambar dengan Media Kain Perca untuk Anak Kelompok B TK Pertiwi 2 Padas - Suyatun, Suyatun (Didaktika, 2022)
Children aged 5 to 6 years have motor skills based on their level of development. Children's fine motor skills cannot develop by themselves but must be developed and trained regularly. One effort that can improve children's fine motor skills is that it can be done by the teacher using creative and fun media. The media used to improve children's fine motor skills is by making collages. From previous research, patchwork media has been proven to be able to increase the attractiveness of students to create something new with better results. The problem in this study was that the researcher wanted to find out how to increase the ability to stick pictures using patchwork media for group B children at Pertiwi 2 Padas Kindergarten with the aim of research to improve children's ability to stick. The research subjects were conducted in group B with a total of 20 children and an age range between 5 to 6 years. With a total of 9 male students and 11 female students. Data collection was obtained from observation and documentation. From empirical data, the initial conditions for the ability to stick to group B children were at an average percentage of 20 in 1 class of 43.75% with the criteria for Starting to Develop (MB) in cycle I increased to 71.46% with the criteria for Developing According to Expectations (BSH). by taking action using patchwork and increasing in cycle II to 86.67% with the criteria of Very Good Development (BSB). So it can be concluded that patchwork media can increase the ability to stick pictures in group B children in Pertiwi 2 Padas Kindergarten